2022
DOI: 10.1371/journal.pone.0266525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrinsic foot muscles training on foot function and dynamic postural balance: A systematic review and meta-analysis

Abstract: This systematic review aimed to analyse the effects of intrinsic foot muscle (IFM) training on foot function and dynamic postural balance. Keywords related to IFM training were used to search four databases (PubMed, CINAHL, SPORTDiscus and Web of Science databases.) for relevant studies published between January 2011 and February 2021. The methodological quality of the intervention studies was assessed independently by two reviewers by using the modified Downs and Black quality index. Publication bias was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Echoing these results, in the present study the resultant MTP joint moment profile was increased, and the joint angle profile was not, therefore the quasi-stiffness of the MTP joint would indeed have increased in the added mass compared with the control condition. While it cannot be confirmed in the present study, the results align with growing evidence that the muscles of the foot are capable of modulating its rigidity [ 38 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…Echoing these results, in the present study the resultant MTP joint moment profile was increased, and the joint angle profile was not, therefore the quasi-stiffness of the MTP joint would indeed have increased in the added mass compared with the control condition. While it cannot be confirmed in the present study, the results align with growing evidence that the muscles of the foot are capable of modulating its rigidity [ 38 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…Dynamic balance improved in all directions in the FG and FHG at both 4 weeks and 8 weeks in the present study, consistent with the recent meta-analysis that also demonstrated the benefit of intrinsic foot exercise on dynamic postural balance (Wei et al, 2022). The addition of tibialis posterior exercises to short foot exercises for the intrinsic foot muscles might result in greater improvements in dynamic balance, as reported in a previous study that added tibialis posterior exercises to the toe curl exercise and showed improved dynamic balance in all directions when compared to performing the toe curl exercise alone (Alam et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…These muscles play important roles in foot posture and function. Previous studies 10 , 34 36 reported that alterations in the function of the intrinsic foot muscles owing to changes in foot posture may lead to variation in foot posture and function. Therefore, further studies on intrinsic foot muscles are needed to clarify the results of the present study.…”
Section: Discussionmentioning
confidence: 99%